UPAYA MENINGKATKAN KINERJA PERUSAHAAN MELALUI EFEKTIVITAS AKTIVITAS BISNIS, TATA KELOLA, DAN OPTIMALISASI PROFIT - Janudin Janudin; Liana Dwi Septiningrum (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
The growth in stock prices reflects the good performance of a company, and the achievement of performance is a manifestation of the availability and good use of capital (in generating profits), business activities run effectively and efficiently, and business risks can be overcome. This means, behind the benefits or goals achieved, there are many factors that influence it. Explicitly, the purpose of this research is to reveal three main factors that are thought to affect bank performance, including capital, business activities and income. The research scope is financial, so the appropriate research model approach is quantitative. To prove this conjecture, linear regression analysis was used. The results reveal that the profitability factor is quite consistent in influencing the growth of bank performance. This is characterized by a positive linear nature, where every time there is a change in profit instruments, the bank's performance has an upward trend. This finding strengthens the argument or reason for the establishment of the company, namely getting profit.